A fundição de sinos do reino para o Brasil na documentação do Arquivo Histórico Ultramarino de Lisboa - Sebastian, Luís (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
Through the study of the documentation from the Arquivo Histórico Ultramarino de Lisboa, this paper tries to understand the administrative process, the responsibilities and the importance of the royal control over the casting and recasting of Brazilian church bells, as a tool of direct control over the Brazilian Church and the development of territorial occupation. The documentation stands out the roll of the Conselho Ultramarino in the centralization of the kingdom’s bell casting, the weaknesses of this system, the general indifference on behalf of the royal power and the fragilities of the Brazilian church